1992
DOI: 10.1002/hep.1840160202
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Infection Persists in the Liver Graft in the Vanishing Bile Duct Syndrome

Abstract: Cytomegalovirus infection is one factor implicated in the cause of the vanishing bile duct syndrome complicating liver transplantation. To further investigate the role of cytomegalovirus in this syndrome, we studied serial liver biopsy material by in situ hybridization for cytomegalovirus DNA using a highly sensitive technique that allows the localization of viral replication. Cytomegalovirus DNA was identified in hepatocytes in 10 of 12 patients with the vanishing bile duct syndrome, 1 of whom had no serologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(58 citation statements)
references
References 20 publications
1
56
1
Order By: Relevance
“…89 Other risk factors include lack of azathioprine (in the cyclosporine era), few histocompatibility leukocyte antigen A and B matches, and grafting a liver from a male donor into a female recipient. 60,89,90 A close relationship has also been found between CMV infection and chronic rejection, as previously mentioned 60,61 ; one study reported a persistent CMV genome in the bile ducts of patients with chronic rejection. 91 Ductopenic rejection is characterized histologically by progressive destruction of the small (interlobular and septal) intrahepatic bile ducts.…”
Section: Chronic Rejectionmentioning
confidence: 75%
See 1 more Smart Citation
“…89 Other risk factors include lack of azathioprine (in the cyclosporine era), few histocompatibility leukocyte antigen A and B matches, and grafting a liver from a male donor into a female recipient. 60,89,90 A close relationship has also been found between CMV infection and chronic rejection, as previously mentioned 60,61 ; one study reported a persistent CMV genome in the bile ducts of patients with chronic rejection. 91 Ductopenic rejection is characterized histologically by progressive destruction of the small (interlobular and septal) intrahepatic bile ducts.…”
Section: Chronic Rejectionmentioning
confidence: 75%
“…59 Indeed, CMV infection may be a risk factor for vanishing bile duct syndrome 59 and chronic liver graft rejection. 60,61 The latter suggestion is supported by in situ hybridization and immunohistochemistry findings of CMV in patients with chronic graft rejection. 62 However, the CMV may not be a causal factor, but rather a consequence of graft injury or an "innocent bystander."…”
Section: Cytomegalovirus Infectionmentioning
confidence: 90%
“…61 In addition, in a number of studies, CMV has been identified as a distinct risk factor for chronic rejection in liver transplantation. 28,53,61,62 Two of these studies have shown the persistence of CMV DNA in the epithelium of bile ducts and endothelial cells of chronically rejected hepatic allografts. 35,62 Although the mechanisms by which CMV infection may cause chronic rejection are uncertain, many investigators believe the combination of direct actions on in- …”
Section: Clinical Risk Factorsmentioning
confidence: 99%
“…VBDS seems to be mediated by immunological factors (T cell-mediated cytotoxicity and alloantibodies) and may be triggered by initial ischemic injury (71). Persistence of CMV DNA in hepatocytes of liver allografts was found only in liver transplant recipients who developed VBDS (72). An increased risk of allograft loss or death has also been related to CMV infection after liver transplantation (45,(73)(74)(75).…”
Section: Type Of Organ Transplantmentioning
confidence: 99%